SEG Technical Program Expanded Abstracts 2015 2015
DOI: 10.1190/segam2015-5876279.1
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Spectral Attributes of Apparent Attenuation: Part 1 - Methodology

Abstract: Ideally, accurate seismic attenuation estimation is extremely useful for reservoir characterization, subtle geological structure identification, and seismic signal compensation. However, seismic attenuation not only distorts their amplitudes but also disperses seismic waves, which gives rise to a number of issues and renders the accurate attenuation estimation impossible. As the measurement of attenuation, the absolute value of quality factor Q does not interest us in seismic interpretation, and the relative v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…A lower peak frequency, as demonstrated by Li et al (2015) is expected to present as positive kurtosis. Positive kurtosis may also be thought of in relationship to bandwidth; a narrower bandwidth from attenuated frequencies should therefore exhibit positive kurtosis.…”
Section: Spectral Kurtosis Attributementioning
confidence: 95%
See 1 more Smart Citation
“…A lower peak frequency, as demonstrated by Li et al (2015) is expected to present as positive kurtosis. Positive kurtosis may also be thought of in relationship to bandwidth; a narrower bandwidth from attenuated frequencies should therefore exhibit positive kurtosis.…”
Section: Spectral Kurtosis Attributementioning
confidence: 95%
“…Gas hydrates are shown to attenuate seismic waves from numerous seismic or well studies Chand and Minshull, 2004;Dvorkin and Uden, 2004;Sahoo et al, 2019, and others), and this effect is even observed in synthetic seismic data created from realworld, hydrate-bearing well log data . To quantify the attenuation response for hydrocarbon accumulations, Li et al (2015 and proposed skewness and kurtosis, two statistical measures, in combination with five other attenuation-related attributes, to measure attenuation in hydrocarbon-filled sediments in both conventional and unconventional reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic interpreters are not usually interested in the absolute attenuation value, but they are usually more interested in the relative attenuation effects between an area and its surroundings. Li et al (2015b) propose a suite of seismic attenuation attributes that quantify the spectral changes between a shallower reference and a deeper target horizon to detect anomalous spectral energy loss. The sketches in Figure 1 summarize these seismic attenuation attributes.…”
Section: Introductionmentioning
confidence: 99%